Penerapan Model Pembelajaran Problem Based-Learning Terhadap Hasil Belajar Matematika Siswa Di Kelas IV Barru - Ferdiansyah, Rian; Syawaluddin, Ahmad; Amirah, Amirah (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2025)
AbstractThis research examines the application of the Problem Based-Learning learning model to improve student learning outcomes in mathematics subjects in class IV UPTD SD Negeri 120 Barru. The approach used is a qualitative approach with the type of research being Classroom Action Research (PTK). The implementation of this action research was carried out in 2 cycles starting with pre-action activities, then each cycle consisted of 4 stages which included planning, implementation, observation and reflection. The subjects of this research were class IV UPTD students at SD Negeri 120 Barru for the 2022/2023 academic year, totaling 22 students. Data analysis was carried out during and after data collection. The data analysis technique used is a qualitative data analysis technique. Based on the data obtained during the implementation of cycle I and cycle II, it was found that the research results in cycle I were in the sufficient category, and there was an increase in cycle II which was in the good category and reached the predetermined indicators. Keywords: Problem Based-Learnig; Learning Outcomes; UPTD SD Negeri 120 BarruAbstrakPenelitian ini mengkaji tentang penerapan model pembelajaran Problem Based-Learning untuk meningkatkan hasil belajar siswa pada mata pelajaran matematika di kelas IV UPTD SD Negeri 120 Barru. Pendekatan yang digunakan adalah pendekatan kualitatif dengan jenis penelitiannya adalah Penelitian Tindakan Kelas (PTK). Pelaksanaan penelitian tindakan ini dilaksanakan dalam 2 siklus yang diawali dengan kegiatan pratindakan, kemudian setiap siklus terdiri dari 4 tahap yang meliputi perencanaan, pelaksanaan, observasi dan refleksi. Subyek penelitian ini adalah siswa kelas IV UPTD SD Negeri 120 Barru tahun pelajaran 2022/2023 yang berjumlah 22 siswa. Analisis data dilakukan pada saat dan setelah pengumpulan data. Teknik analisis data yang digunakan adalah teknik analisis data kualitatif. Berdasarkan data yang diperoleh selama pelaksanaan siklus I dan siklus II diperoleh hasil penelitian pada siklus I berada pada kategori cukup, dan terjadi peningkatan pada siklus II yang berada pada kategori baik dan mencapai indikator yang telah ditentukan. Keywords: Problem Based-Learnig; Hasil Belajar; UPTD SD Negeri 120 Barru